Isolation and Identification of Lactic Acid Bacteria on Boiler Chicken - Roisu Eny Mudawaroch; Setiyono Setiyono; Lies Mira Yusiati; Edi Suryanto (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2020)
Abstract: The aims of this research were to isolate lactic acid bacteria from broiler chicken. The main material was a chicken boiler aged 30 days. The identification of LAB was carried out based on isolation and identification of morphological, phenotypic, and biochemical characteristics. Thirteen LAB isolates were obtained and 5 selected LAB isolates were identified based on growth levels, pH, and lactic acid levels. Five selected LAB isolates were identified as Lactobacillus genus which has Gram-positive, negative catalase, non-motility, hetero-fermentative, rod shapes, rod-colony shapes, and cream colony color.Abstrak: Penelitian ini bertujuan untuk mengisolasi bakteri asam laktat dari ayam broiler. Bahan utamanya adalah ayam boiler berumur 30 hari. Identifikasi BAL dilakukan berdasarkan isolasi dan identifikasi karakteristik morfologi, fenotipik, dan biokimia. Tiga belas isolat BAL diperoleh dan 5 isolat BAL terpilih diidentifikasi berdasarkan tingkat pertumbuhan, pH, dan kadar asam laktat. Lima isolat BAL terpilih diidentifikasi sebagai genus Lactobacillus yang memiliki Gram-positif, katalase negatif, non-motilitas, hetero-fermentatif, bentuk batang, bentuk koloni batang, dan warna koloni krem.